Iran's Struggles for Social Justice : Economics, Agency, Justice, Activism - Vahabzadeh, Peyman (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This interdisciplinary volume offers a range of studies spanning the various historical, political, legal, and cultural features of social justice in Iran, and proposes that the present-day realities of life in Iran could not be farther from the promises of the Iranian Revolution. The ideals of social justice and participatory democracy that galvanized a resilient nation in 1979 have been abandoned as an avaricious ruling elite has privatized the economy, abandoned social programs and subsidy payments for the poor, and suppressed the struggles of women, workers, students, and minorities for equality. At its core, Iran's Struggle for Social Justice seeks to educate and to develop a new discourse on social justice in Iran. .